Engaging in critical language studies - Schwieter, John W., 1979-; Rivera Flores, Jaime Antonio; Iida, Paul Chamness (Readings in language studies., 2022)
The Readings in Language Studies series presents international perspectives on important and emergent themes in language studies: critical pedagogy, language and power, language and identity, second language acquisition, conceptualizations of language, teachers and teaching. Each volume in the series is developed and edited in partnership with the International Society for Language Studies (www.isls.co), an interdisciplinary association of scholars who explore critical perspectives on language. A resource for students and scholars, each themed volume in the series represents the latest thought, literature, research, and methodology in language studies and features authors from across the globe. The series, which includes this current volume, is an essential scholarly resource for universities and personal libraries.